2014
DOI: 10.1007/s40333-014-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change on phenology and primary productivity in the desert steppe of Inner Mongolia

Abstract: Variations in temperature and precipitation affect local ecosystems. Considerable spatial and temporal heterogeneity exists in arid ecosystems such as desert steppes. In this study, we analyzed the spatiotemporal dynamics of climate and vegetation phenology in the desert steppe of Inner Mongolia, China using meteorological data (1961-2010) from 11 stations and phenology data (2004-2012) from 6 ecological observation stations. We also estimated the gross primary production for the period of 1982-2009 and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 32 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…The timing of phenological events is a major determinant of plant productivity and species distribution (Vitasse et al 2011). It is related to seasonal and inter-annual dynamics of vegetation and is highly sensitive to climate variability , Han et al 2015, Keenan and Richardson 2015. Therefore, phenological characteristics can be used as an integrated indicator of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of phenological events is a major determinant of plant productivity and species distribution (Vitasse et al 2011). It is related to seasonal and inter-annual dynamics of vegetation and is highly sensitive to climate variability , Han et al 2015, Keenan and Richardson 2015. Therefore, phenological characteristics can be used as an integrated indicator of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, precipitation was coupled to a shift in maximum NDVI [28]. The restrictive role of minimum temperatures in the growth of subalpine plants requires further study as it is expected to be closely associated with the frequency of frost risk in spring and autumn [35,36].…”
Section: Effects Of Temperature On Shrub Phenologymentioning
confidence: 99%
“…Therefore, species of the LSS grassland need to consume smaller amounts of water per unit of photosynthetic products relative to species of the ESS grassland. Consequently, species of the LSS grassland present more efficient ecophysiological adaptations under drought conditions, and achieve a favorable water balance (Han et al, 2015). Higher water use efficiency at late successional stages is directly connected with higher net production.…”
Section: Figure 4 Relationship Between Leaf Water Potential (ψ) and mentioning
confidence: 99%
“…However, Odum (1985) demonstrated that in stressed ecosystems the expected trends include changes in energetic, nutrient cycling, and community structure and function. In arid and semiarid regions, annual changes in productivity due to changes in precipitation are often much larger than those due to small changes in the composition of vegetation as a result of the improvement or deterioration of the ecosystem (Laycock, 1989;Han et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation